A test of dopamine hyper- and hyposensitivity in alcohol use. (March 2019) - Soder, Heather E.; Webber, Troy A.; Bornovalova, Marina A.; Park, Jong Y.; Potts, Geoffrey F.
Abstract: Biases in outcome processing, mediated by the mesocortical dopaminergic (DA) system, may predict individual differences in the frequency and quantity of alcohol use. We tested the hypothesis that genetic markers associated with increased DA neurotransmission contribute to reduced neural sensitivity to costs and increased alcohol use in an undergraduate sample. We created a DA transmission score using five genetic markers related to DA transmission and assessed neural sensitivity to cost using the feedback-related negativity (FRN), an event-related potential implicated in neural outcome evaluation, on both passive evaluative and active decision-making tasks. Self-reported alcohol use was assessed using the Daily Drinking Questionnaire-Revised. Participants with a higher DA transmission score reported increased alcohol consumption and exhibited a more blunted FRN on both the passive and active tasks. While dopamine hyposensitivity is common among chronic alcohol users, these data provide preliminary evidence that hypersensitivity of the dopamine system may underlie increased alcohol use in those who have not yet developed a chronic alcohol use disorder. Highlights: Dopamine hyper- or hypo-sensitivity may explain variance in alcohol use. Dopamine score was calculated by scoring 5 genetic markers by dopamine availability. Feedback-related negativity to losses and alcohol tendencies were examined. Higher dopamine scores related to blunted feedback-related negativity. Higher dopamine scores also predicted increased alcohol use in college sample.